Seroprevalence and Risk Factors of Chlamydophila abortus Infection in Goats of the State of Rio Grande do Norte, Brazil - Araújo, Juscilânia Furtado; Pinheiro, Raymundo Rizaldo; Andrioli, Alice; Alves, Francisco Selmo Fernandes; Faccioli, Patrícia Yoshida; Eloy, Angela Maria Xavier; dos Santos, Vanderlan Warlington Souza; Peixoto, Renato Mesquita; Lima, Ana Milena Cesar (Acta Scientiae Veterinariae, 2018)
Background: Chlamydophilosis is a disease caused by the bacterium Chlamydophila abortus, responsible for reproductive damage in small ruminants, and economic losses to animal production. In addition, it is classified as a zoonosis once it presents symptoms similar to numerous bacterial and viral infections of the reproductive system, making clinical diagnosis difficult. The objective of this work was to estimate the seroprevalence of anti-C. abortus antibodies in goats and to identify the risk factors for the disease in two mesoregions of Rio Grande do Norte, Brazil. Material, Methods & Results: This research was carried out in two mesoregions of the State of Rio Grande do Norte (Central Potiguar - CP and West Potiguar - WP) located in the Northeast of Brazil. These mesoregions together represent 83% of the regional herd. A total of 54 properties were studied. Those are distributed in seven municipalities: Afonso Bezerra, Angicos, Lages and Pedro Avelino, in the CP mesoregion; and Apodi, Caraúbas, and Mossoró, in the OP mesoregion. We used 540 animals from herds characterized as non-defined breed (NDB) and native breed, regardless of their productive functions, being frequent the consortium of caprine and ovine species. Blood samples were collected through jugular venipuncture by vacuum system with 5 mL tubes without anticoagulant. After collection, the tubes were centrifuged at 1500 g for 15 min. Detection of anti-Chlamydophila sp. antibodies was performed by the Complement Fixation Test. In parallel with the collection, a questionnaire was applied addressing general property and producer characteristics. Seroprevalence of chlamydophilosis in the CP mesoregion was 3.04% (7/230) for the animals and 26.1% (6/23) for the properties, whereas, in the WP mesoregion, the values were 4.2% (13/310) and 35.5% (11/31), respectively. In the final logistic regression model, no variable analyzed was considered to be associated with a higher probability of C. abortus positive properties. There was no significant difference (P = 0.76) in the infection among the studied mesoregions. All the seven municipalities evaluated, had at least one positive property. No serology was found with titers greater than 1:32. The results of the suspects with titers of 1:16 were 3.9% (9/230) in the CP and 3.5% (11/310) in the WP mesoregion. None of the 82 breeding animals tested were C. abortus reagent, but three were suspected. The highest prevalence for the infection was seen in the matrices with 5.6% (18/321), followed by young females with 2.9% (1/35), young males with 1.2% (1/82) and breeding animals with 0% (0/82). Discussion: The seroprevalence to Chlamydophila abortus found in the state of Rio Grande do Norte was lower than that found in most Brazilian states, and even in other countries. The presence of properties with positive animals displays a risk of dissemination of the disease in the region. In addition, the presence of suspect animals may indicate a much larger number of positive animals. The existence of false-negative animals in the herd can lead to difficulties in controlling and eradicating this disease. Although none of the breeding animals were reagent to C. abortus in the CF test, the possibility of venereal transmission should not be discarded. As some animals remained suspects, it may indicate an initial infection phase and seroconversion process, possibly characterizing future transmitters of the bacterium via semen. However, even though seroprevalence was numerically low, this disease should be a cause for concern due to its severity and spread capacity among herds, and especially because it is a zoonosis. We conclude that chlamydophilosis is present in goat breeding in the state of Rio Grande do Norte, Brazil, and female animals are more susceptible to Chlamydophila abortus infection.